An Ion‐imprinted Polymer‐Receptor‐Based Electrochemical Sensor for the Sensitive and Selective Detection of Cadmium. Issue 10 (10th March 2023) - Sadiq, Nauman; Shafique, Muhammad; Akbar, Muafia; Shakoor, Memoona; Mujahid, Adnan; Hussain, Tajamal; Mustafa, Ghulam
Abstract: In this research work, an ion‐imprinted polymer based electrochemical sensor developed for the sensitive and selective detection of cadmium ions in water. Ion‐imprinted and non‐imprinted polymers were synthesized by thermal free‐radical bulk polymerization. Monomer to crosslinker ratio was optimized receptors chemistry and morphology were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Receptors were coated onto interdigital electrodes (IDEs) by spin coating and sensor parameters such as sensitivity, selectivity and reversibility were evaluated by using LCR meter. The fabricated sensor showed concentration dependent linear response with limit of detection of 103 ppb. Selectivity was analyzed in the presence of interfering ions such as Zn 2+, Hg 2+, Cu 2+ and Pb 2+ . The sensor showed a highly selective and reversible response towards cadmium ions. Abstract : An electrochemical sensor fabricated for the detection of cadmium ions in aqueous media. Ion‐imprinted polymer, Interdigital electrodes were used as a receptor and transducer respectively. The fabricated sensor showed highly sensitive, selective and reversible response in term of inductance with lower limit of detection 103 ppb sufficient to monitor the concentration limited by WHO and EPA. The proposed sensor is low cost, small size, robust and easy to operate.